2019
DOI: 10.1007/s00223-019-00520-5
|View full text |Cite|
|
Sign up to set email alerts
|

Rare Inherited forms of Paget’s Disease and Related Syndromes

Abstract: Several rare inherited disorders have been described that show phenotypic overlap with Paget's disease of bone (PDB) and in which PDB is a component of a multisystem disorder affecting muscle and the central nervous system. These conditions are the subject of this review article. Insertion mutations within exon 1 of the TNFRSF11A gene, encoding the Receptor Activator of Nuclear Factor Kappa B (RANK) cause severe, PDB-like disorders including Familial Expansile Osteolysis, Early-onset familial PDB and Expansile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 84 publications
(134 reference statements)
0
41
0
Order By: Relevance
“…According to the original article by Visconti MR et al, the overall frequency of alterations is on average 0.07% among unaffected controls [ 27 ] and, consistently, the allele frequency of p.Pro392Leu in the EXaC database has been reported to be 0.10%. In this regard it is interesting to note that some patients with pathogenic variants in SQSTM1 do not develop PDB but instead present with neurological disease such as amyotrophic lateral sclerosis (ALS) as part of multisystem proteinopathy syndromes [ 28 ] The reason underlying these different presentations remains incompletely understood but there is evidence that digenic inheritance of more than one variant may play a role [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the original article by Visconti MR et al, the overall frequency of alterations is on average 0.07% among unaffected controls [ 27 ] and, consistently, the allele frequency of p.Pro392Leu in the EXaC database has been reported to be 0.10%. In this regard it is interesting to note that some patients with pathogenic variants in SQSTM1 do not develop PDB but instead present with neurological disease such as amyotrophic lateral sclerosis (ALS) as part of multisystem proteinopathy syndromes [ 28 ] The reason underlying these different presentations remains incompletely understood but there is evidence that digenic inheritance of more than one variant may play a role [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing observation that was overlooked by the authors is that PFN1 joins the growing list of genes in which mutations can either cause PDB or other phenotypes such as myopathy, amyotrophic lateral sclerosis, dementia, and Parkinson's disease ( 6–11 ) (Table 1). {TBL 1} The term multisystem proteinopathy (MSP) has been coined to refer to these syndromes.…”
Section: Gene Type Function Pdb Myopathy Als Dementia Glaucomamentioning
confidence: 99%
“…( 9 ) They are characterized by accumulation of abnormal protein aggregates within cells, either because the disease‐causing mutations result in defects of protein degradation through the proteasome or because they act directly to increase the propensity of the mutated protein to form aggregates. ( 6,10 ) It has been known for many years that PFN1 mutations can cause ALS and when the causal mutations from these patients are expressed in vitro , insoluble protein aggregates are formed. ( 11 ) Because the truncating mutation described by Scotto di Carlo and colleagues seems to do the same when proteasomal degradation is inhibited by MG163, it looks as though PFN1 might be a candidate for a new form of MSP, which I provisionally have named MSP7.…”
Section: Gene Type Function Pdb Myopathy Als Dementia Glaucomamentioning
confidence: 99%
“…Genetic factors play an important role in PDB. Many genetic variants have been identified that predispose to PDB and related syndromes1 2 but mutations in sequestosome-1 ( SQSTM1 ) are the most important predisposing factor, occurring in up to 50% of patients with a family history of PDB and up to 10% of people who are unaware of having a family history 3–8. Carriers of SQSTM1 mutations have more severe disease with an earlier age at onset than patients who do not carry mutations 9.…”
Section: Introductionmentioning
confidence: 99%